(untitled) (International Seven Journal of Multidisciplinary, 2025)
The sunflower develops in phases that reflect the development and maturation of the plant and the knowledge of its crop coefficient (Kc) can help to improve management and increase productivity. The objective of this study was to determine the Kc curve of the sunflower cultivar BRS 323 in the northwest of Minas Gerais. The experiment was carried out in a protected environment at the Federal Institute of Northern Minas Gerais – Arinos Campus, with cultivation in pots of 25 L volume. These pots had at the bottom a filter composed of gravel, shade screen and, on top of it, 24 L of a Dystroferric Red Latosol. Drains with low-density polyethylene tubes were installed at the bottom of the vessels, so that they served as drainage lysimeters. Irrigation management was based on soil water balance by determining the actual crop evapotranspiration (ETr) using lysimeters. The reference evapotranspiration (Eto) was determined using the EVAPO mobile software. The daily Kc were determined by the ratio between ETrc and Eto. The duration of the crop phases was determined visually, by the anatomy of the plant, especially the inflorescence. The leaf area index (L) was determined by the ratio between the total leaf area (m²) and the soil surface area (useful area of the pot in m²). The Kc and L were associated by multiple regression using the SISVAR statistical software, after finding a significant relationship by the F test. The initial stage of the sunflower lasted 6 days and the Kc1 was constant with a value equal to 0.6. The vegetative development stage lasted 25 days and Kc2 ranged linearly from 0.6 to 1.78. The flowering phase, represented by Kc3, lasted 34 days and the value found was 1.8. The physiological maturation phase lasted 9 days and Kc4 ranged linear and decreasing between 1.8 and 0.74. It was observed, in this study, that the culture coefficients differ from those found in the literature, as they vary according to the cultivar, the boundary conditions and the method of determination of Kc (single Kg). Further studies are needed to determine the Kc under field conditions and correlate it with the Kc obtained in a protected environment.